Quercetin protects jejunal mucosa from experimental intestinal ischemia reperfusion injury by activation of CD68 positive cells - Curgali, Kristina; Toth, Stefan; Jonecova, Zuzana; Maretta, Milan; Kalpakidis, Theodoros; Petriskova, Ivana; Kusnier, Matus; Soltes, Jan; Svana, Martin; Caprnda, Martin; Delev, Delian; Rodrigo, Luis; et al. (Acta histochemica, 2018)
The aim of our study was to analyse the possible protective effect of quercetin application during the jejunal ischemia-reperfusion injury (IRI) in rats. Quercetin was administered intraperitoneally 30min before 1h ischemia of superior mesenteric artery with following 24h lasting reperfusion period. The male specific pathogen-free (SPF) Charles River Wistar rats were used. In the group with applied quercetin, the significantly increased (p<0.001) levels of anti-inflammatory cytokine IL10 were observed both in the blood serum and jejunal tissue. The improvement of the mucosal tissue morphology and proliferating and DNA repairing cell number measured by PCNA activity were recorded by more than 30% higher in the quercetin group. Simultaneously, significant elongation of the intestinal glands (p<0.001) and increase in the number of CD68-positive cells in the lamina propria mucosae (p<0.001) in comparison with control group were found. Based on our results, the preventive application of quercetin before induction of jejunal IRI stimulates faster jejunal mucosa restoration and it seems to have immunomodulatory and anti-inflammatory effects as well. CD68-positive macrophages could have crucial role in this process since they work as both growth factor and cytokine producers.
Keywords: quercetin; jejunum; Rats; Quercetin; Jejunum; antiflogistika; antigeny diferenciační myelomonocytární; Small intestine; reperfuzní poškození; Gastric Mucosa; mužské pohlaví; Ischemia-reperfusion injury; Reperfusion Injury; Antigens, Differentiation, Myelomonocytic; krysa rodu Rattus; CD68 positive cells; zvířata; Anti-Inflammatory Agents; IL10; Antigens, CD; žaludeční sliznice; CD antigeny; Male; Animals